ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA BERINVESTASI DI PASAR MODAL PADA MASA PANDEMI COVID-19 (Studi Pada Mahasiswa Prodi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Macika Ika Purnama; Moh. Amin; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the effect of technological developments, investment knowledge, capital market knowledge, investment returns, investment risk, and motivation on investment interest in the capital market during the Covid-19 pandemic. The population in this study were students of the Faculty of Economics and Business, Islamic University of Malang which consisted of students of the 2018 Accounting Department. The technique used in the sampling was purposive sampling technique, the selected sample was 105 respondents. It is a type of survey research that uses quantitative methods by distributing questionnaires (questionnaires). This study uses multiple linear regression analysis with the help of SPSS 16. The results show that: a). Technological developments do not affect student interest in investing in the capital market during the Covid-19 pandemic. b). Investment knowledge does not affect student interest in investing in the capital market during the Covid-19 pandemic. c). Capital market knowledge affects students' interest in investing in the capital market during the Covid-19 pandemic. d). Investment returns do not affect student interest in investing in the capital market during the Covid-19 pandemic. e). Investment risk does not affect student interest in investing in the capital market during the Covid-19 pandemic. f). Motivation affects student interest in investing in the capital market during the Covid-19 pandemic.Keywords: Technology development, Investment knowledge, Capital market knowledge, Investment return, Investment risk, Motivation